2004
DOI: 10.1128/jcm.42.8.3837-3840.2004
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of a New Screening Test That Detects Clostridium difficile in Fecal Specimens

Abstract: Clostridium difficile causes approximately 25% of nosocomial antibiotic-associated diarrheas and most cases of pseudomembranous colitis. We evaluated C. DIFF CHEK, a new screening test that detects glutamate dehydrogenase of C. difficile. Our results showed that this test was comparable to PCR in sensitivity and specificity and outperformed bacterial culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 24 publications
2
40
1
1
Order By: Relevance
“…This highlights the high negative predictive value of the GDH screen relative to culture, which has also been evaluated relative to CCNA (31,34,37). GDH screening is less specific, which may reflect antigenic homology among clostridia, as was suggested by a false-positive rapid stool toxin test result for a patient with Clostridium sordellii bacteremia (13).…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the high negative predictive value of the GDH screen relative to culture, which has also been evaluated relative to CCNA (31,34,37). GDH screening is less specific, which may reflect antigenic homology among clostridia, as was suggested by a false-positive rapid stool toxin test result for a patient with Clostridium sordellii bacteremia (13).…”
Section: Discussionmentioning
confidence: 99%
“…The PPV of 21.4% for GDH alone confirmed the need to pursue additional testing of GDHpositive/toxin or PCR negative specimens to resolve these specimens as positive or negative for C. Difficile toxin. Zheng et al (26) reported that the Techlab C. diff Chek-60 GDH assay had good sensitivity compared to CYT testing of 92%, but it had a low specificity of 89.1% and poor positive predictive value (PPV) of 57.7%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increased sensitivity of the assay, GDH antigens appear both in toxigenic and non-toxigenic strains, allowing for the detection of both variants in patient samples. Upon the identification of antigen in stool samples using a GDH ELISA, the presence of C. difficile should be confirmed using an alternate method because it has low specificity despite its high sensitivity (12).…”
Section: Discussionmentioning
confidence: 99%
“…A positive result (optical density [OD] Ͼ 0.10) supported the detection of toxigenic C. difficile. Colonies on CCFA with typical characteristics of C. difficile (flat yellow colonies) were tested by PCR in an internally validated PCR assay targeting the putative toxin repressor gene tcdC (primers 5=-TCTAGCTAATTGGTCATAAG-3= and 5=-AATAGCAAATT GTCTGAT-3=) and the GDH "common-antigen" gene (gdh) using published primers (33). Despite variability in other regions of the PaLoc, the tcdC primers bind conserved regions in all toxigenic strains of C. difficile in GenBank (evaluated in August 2005) and over 1,200 sequenced strains in a recent survey (4).…”
Section: Methodsmentioning
confidence: 99%